HUBUNGAN ANTARA MOTIVASI BELAJAR DENGAN KEMAMPUAN BERPIKIR TINGKAT TINGGI PADA MATERI SISTEM PENCERNAAN KELAS XI SMA MINHAJUTH THULLAB WAY JEPARA - Saroh, Dewi; Mulyani, HRA; Susanto, Handoko (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2025)
The aim of this research is to explore how student motivation for learning connects with their advanced thinking skills regarding the digestive system topics in class XI IPA at SMA Minhajuth Thullab. This study employs an ex post facto design, which means it analyzes data collected after events have occurred. A saturated sampling method was used in this research. The study followed a quantitative approach, utilizing the ex post facto method alongside a correlational framework to investigate existing cause-and-effect links. According to the validation test results where rxy ≥ rtable: 0. 98 > 0. 63, it can be affirmed that the questions are valid. The outcomes from the hypothesis testing, analyzed through the r test, show that the results yielded t (5. 74, 1. 69), establishing a correlation. These findings indicate that there is indeed a connection between students' learning motivation and their high-level thinking skills. This conclusion is backed by the fact that t count surpasses t table: t count 5. 74 > t table 1. 69. Hence, there exists a strong correlation between learning motivation and high-level thinking skills, represented by an r value of 0. 703. Furthermore, the increase in learning motivation corresponds with an enhancement in high-level thinking skills, specifically by a factor of 0. 04. Therefore, the link between learning motivation and high-level thinking abilities in students regarding the digestive system content in class XI IPA at SMA Minhajuth Thullab is both very strong and significantly high.